Simulation as a service (SMaaS): a cloud-based framework to support the educational use of scientific software. (1st January 2014) - Bitterman, Thomas; Calyam, Prasad; Berryman, Alex; Hudak, David E.; Li, Lin; Chalker, Alan; Gordon, Steve; Zhang, Da; Cai, Da; Lee, Changpil; Ramnath, Rajiv
Large manufacturers increasingly leverage modelling and simulation to improve quality and reduce cost. Small manufacturers have not adopted these techniques due to sizable upfront costs for expertise, software and hardware. The software as a service (SaaS) model provides access to applications hosted in a cloud environment, allowing users to try services at low cost and scale as needed. We have extended SaaS to include high-performance computing-hosted applications, thus creating simulation as a service (SMaaS). Polymer portal is a first-generation SMaaS platform designed to integrate access to multiple modelling, simulation and training services. Polymer portal provides a number of features including an e-commerce front end, common AAA service, and support for both cloud-hosted virtual machine (VM) images and high-performance computing (HPC) jobs. It has been deployed for six months and has been used successfully for a number of training and simulation activities. This paper describes the requirements, challenges, design and implementation of the polymer portal.